HEALTH SERVICES IN THE WORLD HEALTH ORGANIZATION MULTICOUNTRY SURVEY PAKISTAN AND ITS ASSOCIATION WITH MATERNAL AND NEW-BORN OUTCOME - Mazhar, Syeda Batool; Batool, Afshan; Ain, Qurra-tul (Journal of Ayub Medical College Abbottabad, 2018)
ABSTRACT: Objective: To determine the availability of essential obstetric and newborn care at referral level facilities of Pakistan that were selected for World Health Organization multicountry survey for maternal and newborn health and to correlate it with maternal and neonatal outcomes. Methods: This cross-sectional study assessed the infrastructure, equipment, services and staffing in 16 referral level government hospitals participating in World Health Organization multicountry survey for maternal and newborn health from 1st March to 30th May, 2011. This data was correlated with maternal & neonatal outcomes of each facility using chi square test (Statistical Package for Social Sciences 18) Results: The studied facilities had basic infrastructure, most components of Essential Maternal and Neonatal Obstetric Care services with part time/full time availability of obstetricians, anesthetists and pediatricians. Adult intensive care unit was available in 68%, and neonatal intensive care unit was available in half of the facilities. The incidence of severe maternal outcomes had a positive correlation with presence of adult intensive care unit, mechanical ventilator and twenty four hours (24/7) availability of anesthesiologist, nurses & paramedics. The neonatal mortality was also higher in facilities with neonatal intensive care unit facility. Conclusion: Most components of Essential Maternal and Neonatal Obstetric Care services facilities were present in the studied facilities.Tertiary level facilities even with availability of Adult and neonatal intensive care units had more adverse maternal and newborn outcomes perhaps due to more disease burden. Keywords: EMONC; facility; severe maternal outcome; maternal mortality; perinatal mortality Background: WHO MCS in 2011 evaluated the incidence and management strategies linked with maternal and neonatal mortality in facilities across 26 countries including Pakistan. This study, a sub-analysis assessed the availability of essential obstetric and newborn care at referral level facilities of Pakistan that were selected for WHO MCS to correlate it with maternal and neonatal outcomes. Methods: This cross-sectional study assessed the infrastructure, equipment and services in 16 referral level government hospitals participating in WHO MCS from 1st March to 30th May, 2011. The association was found between this data and maternal & neonatal outcomes of each facility using chi square test. Results: The studied facilities had basic infrastructure, most components of Essential Maternal and Neonatal Obstetric Care services with part time/full time availability of obstetricians, anaesthetists and paediatricians. Adult intensive care unit was available in 68%, and neonatal intensive care unit was available in half of the facilities. The incidence of severe maternal outcomes had a positive correlation with presence of adult intensive care unit, mechanical ventilator and twenty-four hours (24/7) availability of anaesthesiologist, nurses & paramedics. The neonatal mortality was also higher in facilities with neonatal intensive care unit facility. Conclusion: Most components of Essential Maternal and Neonatal Obstetric Care were present in the studied facilities. Tertiary level facilities even with availability of Adult and neonatal intensive care units had more adverse maternal and new-born outcomes perhaps due to more disease burden. Keywords: EMONC; facility; severe maternal outcome; maternal mortality; perinatal mortality